Global trend of research and development in education in the pandemic era: A systematic literature review - H. Husamah; Hadi Suwono; Hadi Nur; Agus Dharmawan (Universitas Muhammadiyah Malang, 2022)
Research and Development (R&D) has urgency in education, especially during a pandemic because it describes solutions and innovations. The purpose of this systematic literature review (SLR) was to analyze the global trend of research and development in education in the pandemic era. We used the word “research and development education” in the disbursement menu in the SCOPUS database, and after applying the inclusion and exclusion criteria using the PRISMA technique, we found 15 suitable articles. There is an increasing trend of research on R&D in the last three years, where the peak of publication occurs in 2021 and decreases in 2022. More articles are published by authors from Europe. Articles are dominated by international collaborations. The R&D article is related to sustainable development and is closely related to educational innovation, especially at the university level. Based on the co-citation data presented by VOSviewer, there is a relationship between R&D and COVID-19. It can be concluded that R&D in education gets special place and attention from researchers in the world.